SÍNTESE DE PÓS DE α-ALUMINA COM ADIÇÃO DE SEEDS ATRAVÉS DO MÉTODO PECHINI - Salem, Raphael Euclides Prestes (2012)
Alumina is a ceramic material of great technological importance, due to its mechanical, electrical, thermal and optical properties. At industrial scale, alumina is obtained from bauxite, by the Bayer process. By this process, α phase, the most stable one, is obtained at temperatures above 1200°C, through a reconstructive transformation of its precedent transition phase, followed by nucleation and growth of particles. With the advance of technology, chemical methods for synthesis of powdered materials have been much studied, due to the need to obtain materials with improved properties. Pechini method was a method developed in the decade of 1960 in order to obtain ceramic oxides through simple procedures and using relatively low temperatures, allowing the production of materials with smaller particle size, controllable properties and high purity. This work aims to synthesize α-alumina powders by Pechini method with addition of α-alumina seeds, thus promoting the formation of α-phase in lower temperature than in the traditional methods. Also, the objective is to study the influence of an oxygen flow in the calcination process and in the elimination of organic matter from the precursor resin. After the synthesis and the formation of precursor resins, the obtained samples with and without the addition of seeds were calcined at temperatures between 500°C a nd 1100°C. The precursor resins were characterized by infrared spectroscopy and differential thermal analysis associated with thermogravimetry, and the calcined powders were characterized by differential thermal analysis associated with thermogravimetry, X-ray diffraction, infrared spectroscopy and scanning electron microscopy. The seeding process promoted a significant reduction in the temperature of formation of α-phase, consequently allowing to form particles with smaller crystallite size, although as strong agglomerates irregularly shaped. The incidence of an oxygen flow on the calcination process contributed in a less significant way to eliminate the residual organic matter, present in the calcined samples even at high temperatures. It is observed that seeding the reaction medium is a simple method to favor the phase transformation of alumina through a mechanism of diffusional nucleation, promoting the formation of α-phase at lower temperatures.